(untitled) (The Journal of Academic Development, 2023)
This study has focused on students’ performance level that is affected by different aspects. Research has been centered on bachelor-level students’ English subjects at a community campus at Rupandehi, Nepal. The study is based on quantitative approaches supported by qualitative discussions. Data collection was conducted via a Google Forms questionnaire, including interviews. This study has revealed different levels of performance of the students and the aspects affecting them. Especially, the varied background of the students’ and their competencies are the major factors of their performances. Besides, appropriate addresses of bridging supports would be more effective in increasing the performance. In the same way, library improvement, technological facilities, extra time classes according to student’s convenience, scheduled orientation cum motivational programs etc., would increase the expected outcome towards students’ performance. Similarly, the application of modern techniques/technologies to be applied while studying, students’ financial status, additional student-focused initiatives by campus, etc., were asked to the students and seen as affecting the students’ better performances. And, students’ self-motivation towards effective English learning is also a vital part as suggested by the interviewee student.